Broncoscopic Myths and Legends: The Use of Fiberoptic Bronchoscopy to Guide Percutaneous Tracheostomy. Issue 6 (November 2016) - Pancoast, Thomson C.; Bowling, Mark R.; Anciano, Carlos J.
Abstract : Percutaneous dilatational tracheostomy can be performed blindly on the basis of the identification of landmarks alone or using fiberoptic bronchoscopy or ultrasonography to guide the procedure. There is controversy regarding the use of bronchoscopic guidance for the procedure. We have evaluated the literature to determine the utility of this practice.